SAT0165 The effect of alendronate on age-specific incidence of key osteoporotic fractures. (1st June 2001) - Hochberg, M; Thompson, D; Black, D; Quandt, S; Cauley, J; Geusens, P
Abstract : Background: Objectives: To describe the behaviour of the relative risk (RR), absolute risk reduction (ARR), and number needed to treat (NNT) by attained age for the hip, spine or forearm for alendronate treatment in women with osteoporosis. Methods: 3658 women with osteoporosis from the Fracture Intervention Trial were followed for 3 to 4.5 years and treated with alendronate (ALN) at 5 mg/day for 2 years followed by 10 mg/day for the remainder of the trial. The age groups used in the analysis were: 55–65, 65–70, 70–75 and 75–85. All fractures were confirmed by x-rays. Results: Risk reduction of hip, spine and forearm fractures were 53% (RR = 0.47, p < 0.01), 45% (RR = 0.55, P < 0.01) and 30% (RR = 0.70, p = 0.038) respectively. The reductions did not depend on age. The ARR increased with age for each of the fracture sites. For the hip, the ARR increased from 0.13 women per 100 patient-years at risk (PYR) for the 55 to 65 group to 0.53 women per 100 PYR for the 75 to 85 group. The corresponding increases in ARR for the spine were 0.14 and 0.86. The NNTs for 5 years for the hip were 157 for the 55–65 year old and 45 for the 75 to 85 year old women. The corresponding numbers for the spine were 140 and 23. For the composite endpoint, the NNTs (for 5 years) were 38, 25, 17 and 13 for the age groups 55–65, 65–70, 70–75 and 75–85 respectively. Conclusion: Alendronate is very effective in reducing the risk of osteoporotic fractures, regardless of age.